The effect of technological innovations, urbanization and economic growth on environmental quality: does governance matter? - Khan, Hayat; Khan, Itbar (Frontiers in Environmental Science, 2023)
Climate change has become a major challenge in recent decades as a result of rapid economic growth due to increased energy use and a rise in urbanization. Environmental damage induced by energy use, urbanization, and economic growth can be overcome by technological advancement and good governance. This study examines the effect of urbanization, technological innovations, and economic growth on carbon dioxide emissions in the Belt and Road initiative countries from 2002 to 2022. By using GMM model, the results show that, technological innovations and foreign direct investment raise carbon dioxide emissions however, research and development enhance environmental quality. This study also found that urbanization has a nonlinear relationship with carbon emission where effective governance exert a moderating role in this association. This study provides important policy suggestions for BRI countries.